The role of depression, eating disorder symptoms, and exercise in young adults' quality of life. (December 2018) - Trojanowski, Paige J.; Fischer, Sarah
Abstract: Objective: Eating disorder (ED) symptoms are negatively associated with quality of life (QOL), while exercise is typically positively associated with QOL. Past studies have not examined the relative contribution of depression to this outcome. This study examined the influence of ED symptoms, exercise frequency, and exercise motivation on global QOL in undergraduates while accounting for the shared relationship between ED symptoms and depression. Method: Students ( N = 851) completed the EDE-Q, Reasons for Exercise Inventory, BDI-II, Quality of Life Inventory, and a 1-month exercise timeline followback calendar. Hierarchical regression analyses were conducted to examine the relative contributions of ED symptoms, depression, and exercise variables to QOL. Results: Shape concern and BDI-II scores accounted for significant variance in QOL scores. Depressive symptoms, however, accounted for 9.55% of the unique variance in QOL, while shape concern accounted for only 0.77%. Exercise frequency did not explain significant variance in QOL. The motivations of exercising for mood improvement and for enjoyment explained significant variance in QOL. No interactions between exercise frequency and exercise motivations were significant. In the final model, identifying as a woman was associated with decreased QOL. Discussion: Results suggest that studies examining the impact of disordered eating and exercise on QOL should account for depression due to depression's high comorbidity with EDs and its influence on exercise behavior and motivation. Additionally, results support findings that factors such as exercise motivation may better account for differences in QOL than exercise frequency. Highlights: Depression accounts for more variance in quality of life than ED symptoms. Shape concern but not other ED symptoms influence college students' quality of life. Reasons for exercise impact quality of life more than exercise frequency.